Les sources de la crainte: analyse littéraire d’une émotion « primaire » en Mésopotamie - Villard, Pierre (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2026)
Today, emotions are studied using various approaches: historical, lexical, iconographic, or a combination of these. A new way of approaching the question of fear is to examine its causes. What specific situations are most likely to provoke fear? And how were the emotions associated with fear defined in different situations?